The Influence of Entrepreneurship Education, Self Efficacy and Locus of Control on Students' Entrepreneurial Intentions in Yogyakarta - Silvia Janna Vingki; Ranto, Dwi Wahyu Pril (Asian Journal of Management Analytics, 2023)
Students as agents of change need to be encouraged to engage in entrepreneurial activities. The first step that can be taken is to grow their intention in the world of entrepreneurship. This activity can be done by providing entrepreneurial knowledge in college. This study aims to examine the effect of entrepreneurship education, self-efficacy and locus of control on students' entrepreneurial intentions. The population in this study were students at private universities in Yogyakarta. The sampling technique in this study used the purposive sampling method, namely selecting samples that matched the criteria used for the study. The criteria for the sample taken are students who have taken or are currently taking entrepreneurship courses. While the data collection method using a questionnaire. The number of respondents who were selected as samples was 101. The data analysis used in this study was multiple regression analysis. Based on the results of the study, it was found that entrepreneurship education, self-efficacy and locus of control had an effect on students' entrepreneurial intentions.